The teaching-learning process of the tactics in the Soccer - Reynerio Torres-Tarazón; Ángel Luis Román-Hernández; Neibis Padilla-Gámez (Universidad de Guantánamo, 2015)
Inside the process teaching-learning of the soccer, the tactical preparation occupies an important place. The present work has like topic: The process of teaching-learning of the tactics in the Soccer. The scientific problem is given in: How to increase the defensive tactical preparation in the soccer athletes? As objective we do intend to base aspects theoretical generals of the defensive tactics in the Soccer. The used methods are, theoretical: historical-logical, analysis-synthesis; empiric methods: documental analysis. By means of the analysis of the literature, the insufficient treatment was evidenced that has had the preparation tactical-defensive in the athletes.